Catalytic Ozonation Treatment of Coal Chemical Reverse Osmosis Concentrate: Water Quality Analysis, Parameter Optimization, and Catalyst Deactivation Investigation - Qin, Yihe; Yuan, Run; Wang, Shaozhou; Zhang, Xuewei; Luo, Shaojun; He, Xuwen (Toxics (Basel), 2024)
Catalytic ozone oxidation, which is characterized by strong oxidizing properties and environmental friendliness, has been widely used in organic wastewater treatments. However, problems such as a low organic pollutant removal efficiency and unstable operation during the catalytic ozone treatment process for wastewater remain. To address these disadvantages, in this study, the treatment efficacy of catalytic ozone oxidation on a coal chemical reverse osmosis concentrate was investigated. The basic water quality indicators of the chemical reverse osmosis concentrate were analyzed. The effects of initial pollutant concentration, pH, ozone concentration, and catalyst concentration on the COD removal rate from the coal chemical reverse osmosis concentrate were explored. Water quality indicators of the chemical reverse osmosis concentrate before and after the catalytic ozone treatment were studied using spectroscopic analysis methods. The RO concentrate demonstrated large water quality fluctuations, and the catalytic ozonation process removed most of the pollutants from the treated wastewater. A possible deactivation mechanism of the ozone catalyst was also proposed. This study provides a theoretical reference and technical support for the long-term, efficient, and stable removal of organic pollutants from coal chemical reverse osmosis concentrate using a catalytic ozone oxidation process in practical engineering applications.